Discovery of stereospecific cytotoxicity of (8R, 8′R)-trans-arctigenin against insect cells and structure-activity relationship on aromatic ring. Issue 13 (1st July 2020) - Yamauchi, Satoshi; Nishimoto, Asuka; Nishiwaki, Hisashi; Nishi, Kosuke; Sugahara, Takuya
Graphical abstract: Abstract: One of the arctigenin stereoisomers, (8 R, 8′ R )- trans -form 1, showed stereospecific cytotoxicity against insect cells, Sf9 and NIAS-AeAl-2 cells. By the comparison with other stereoisomers, the most importance of the 8′ R stereochemistry for the higher activities was clarified. On the other hand, the wider range of activity level among stereoisomers against cancer cells, HL-60, was not observed. The structure-activity relationship research using derivatives bearing (8 R, 8′ R )- trans -form was performed to show the same level of activities of 3-iodo, 4-iodo, and 3, 4-methylenedioxy derivatives 28, 29, and 36 as (8 R, 8′ R )- trans -arctigenin 1 . In the examination of thiono derivatives, 4-iodo thiono and 3, 4-methylenedioxy thiono derivatives 66, 67 showed similar level of activities to that of (8 R, 8′ R )- trans -arctigenin 1 . The expression of ribosomal 28S rRNA gene of Sf9 cells was increased by (8 R, 8′ R )- trans -arctigenin 1, whereas a degradation of DNA was not observed.